The portrait of spiritual intelligence and aggressiveness of university students - M. Nawa Syarif Fajar Sakti; Syahirul Alim (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
Aggression is interpreted as a behavior that aims to hurt others physically and verbally. This study used quantitative approach through correlational method to find out the influence of spiritual intelligence (SQ) to the aggressiveness in university students. Students’ aggressiveness was measured using adapted aggression questionnaire, while SQ was measured using the adapted spiritual intelligence scale. The sample technique used proportional random sampling technique and data analysis used regression test through SPSS 22. The findings of the research suggest that spiritual intelligence has a positive and significant effect on students’ aggressiveness. The research results point out that SQ among the students encourages God spot activation. God spot leads students to show ideal behavior and find peaceful solution for every problem. God spot makes students crave on the transcendence; as the consequence, the deep love, peaceful, unity of existence arise in students’ mind and behavior. The peaceful behavior significantly decreases students’ aggressiveness